PO259 Population-based study of prognostic value and control of nocturnal bp after tia and stroke. (1st December 2017) - Kubiak, Magdalena M; Lovett, Nicola; Webb, Alastair; Wharton, Rose M; Rothwell, Peter M
Abstract : Background: In previous studies of treated hypertensives, nocturnal-BP was a stronger predictor than daytime-BP of residual risk of stroke and cardiovascular events (CVEs). However, it is unclear whether nocturnal hypertension (NH) explains residual risk of recurrent stroke after TIA/ischaemic stroke. Methods: In a population-based study (Oxford Vascular Study), consecutive patients with TIA/non-disabling stroke had 24 hour ambulatory BP-monitoring (ABPM) at one-month follow-up. Mean daytime and mean night-time-BP were related to risk of recurrent stroke and cardiovascular events on follow-up after age/sex-adjustment. NH was defined as asleep mean SBP ≥120 mmHg and daytime-hypertension (DH) as awake mean SBP ≥140 mmHg. Results: Among 1035 patients with ABPM (mean/SD age 68.67/12.74), 372 (36.4%) had residual NH and 190 (18.4%) had residual DH (p<0.0001). However, mean asleep and mean awake BP only weakly predicted cardiovascular events (n=92; HR/SD: 1.19, 95% CI 0.99–1.39; and 1.19, 0.97–1.39, respectively). Neither NH (HR=1.37, 0.87–2.16) nor DH (HR=1.67, 0.99–2.77) predicted recurrent stroke (n=76). Indeed, residual DH tended to be more predictive of all cardiovascular events (HR=1.68, 1.06–2.66 vs 1.12, 0.73–1.71). Conclusion: Residual nocturnal hypertension was more common than daytime hypertension, but it was not a major risk factor for stroke or cardiovascular events.